The synergetic effect of Lean Six Sigma and TRIZ on the improvement of an electronic component - Araújo, Sónia (2021)
Continuous improvement is a constant concern of companies operating in strongly competitive markets. This means to be constantly unsatisfied with the company status-quo, searching for opportunities to improve. The goal is to increase business efficiency and effectiveness, providing value to the client. In a fast-paced compass industry with complex products, the combination of strategies that bring such value is preferred. To that, the authors proposed to combine synergistically Lean Six Sigma and TRIZ to improve an electronic component of an instrument system in a first-tier automotive industry. This component that had an insignificant cost (1MU maximum) had a high rejection rate provoking complaints and losses that reached a loss of 156 189 MU. This motivated the company to define a project and allocate resources to it. Thus, the project was allocated and developed in the context of an Industrial Engineering and Management master dissertation by the first author of this paper under an action-research strategy. The main results were a decrease of 83% of defects per million opportunities and savings higher than 50 000 MU.